Effect of Narrative Classroom Guidance on Generation Alpha Students' Emotional Regulation - Nurul Azmi Saragih; Hafiz Ahmad Khan; Budi Astuti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to determine the effect of basic classical guidance services with a narrative approach on optimizing the emotional regulation of Generation Alpha students at SMP Negeri 8 Medan. The phenomenon of low emotional regulation ability in Generation Alpha students represents a specific urgency requiring intervention based on guidance and counseling services. The method used is a quasi-experimental design with a nonequivalent control group pretest-posttest design. The research sample consisted of 32 students in the experimental class and 29 students in the control class selected through purposive sampling technique. The data collection instrument used an emotional regulation questionnaire developed based on Gross's indicators in Putra et al. (2014), covering: strategies to emotion regulation, engaging in goal directed behavior, control emotion response impulse, and acceptance of emotional response. Hypothesis testing using the Independent Sample t-test showed a t-count value of 7.842 with sig. (2-tailed) = 0.000 < 0.05, so H₀ was rejected and H₁ was accepted. The mean posttest value of the experimental class (87.34) was significantly higher than the control class (68.17). Cohen's d effect size = 2.886 indicates a very large effect. The conclusion confirms that basic classical guidance services with a narrative approach significantly affect the optimization of emotional regulation of Generation Alpha students at SMP Negeri 8 Medan.